FRI0103 One-year follow-up of a nationwide cohort of patients with inflammatory arthritis, who switched from originator to biosimilar etanercept, focusing on patients who switched back to originator. an observational danbio study. (12th June 2018) - Glintborg, B.; Sørensen, I.J.; Omerovic, E.; Mehnert, F.; Manilo, N.; Danebod, K.; Jensen, D.V.; Nordin, H.; Loft, A.G.; Hendricks, O.; Chrysidis, S.; Andersen, B.L.; et al.
Abstract : Background: In Denmark, patients (pts) treated with originator etanercept (ETA) 50 mg SC conducted a mandatory non-medical switch to biosimilar SB4 in April 2016 ( switchers). Pts treated with 25 mg ETA or 50 mg powder-solution were not mandated to switch ( non-switchers). Some switchers resumed ETA during follow-up ( back-switchers) . Objectives: To investigate the frequency of back-switching after the non-medical switch from ETA to SB4, and in back-switchers to study, 1) baseline characteristics at the time of initial switch (ETA->SB4), 2) reasons for SB4 withdrawal, 3) changes in disease activity during treatment with SB4 and after back-switching. Methods: Patient data were retrieved from the DANBIO registry (censored August 2017). For back-switchers, disease activity at the start of SB4 (=baseline) and at the time of back-switching to ETA were compared, and changes in disease activity between the two time points were calculated (=delta values), stratified by indication (RA/PsA/AxSpA). Baseline characteristics of back-switchers were compared to the rest of the switch population (Chi-sq, Mann-Whitney U-test). Abbreviations are shown in table 1. Results: 1641 pts switched from ETA to SB4. Of these, 299 (18%) withdrew SB4 therapy during 1 year follow-up and either switched back to ETA (n=120, 7%), started another bDMARD (n=104), died (n=9), were lost to follow-up (n=1) or did not re-start bDMARDs (n=65). Among the 120 back-switchers, SB4 was withdrawn due to LOE (52%), AE (39%), or other/unknown reasons (9%). The reasons for withdrawal of SB4 in back-switchers are listed in table 1. No major safety events occurred. The median time on SB4 before back-switching was 120 (IQR 73–193) days, and the time between stop of SB4 and re-start of ETA was 1 1–1 days. Baseline characteristics of back-switchers vs the rest of the switch population were similar (all p>0.05). Among back-switchers who stopped SB4 due to LOE, PGA increased during SB4 treatment, whereas CRP and SJC were largely unchanged (table 1). At the date of censoring, 104/120 back-switchers (87%) were still treated with originator ETA (median treatment duration 236 (155–302) days). Conclusions: In a nationwide cohort of 1621 arthritis patients that were switched from ETA to SB4, 7% switched back to ETA. Back-switchers had no distinct clinical or disease characteristics upon start of SB4. AEs prior to back-switching were largely unspecific. In pts who withdrew SB4 due to LOE, PGA had increased. Reasons for back-switching appeared to be predominantly subjective rather than objective (nocebo effect). Originator drug was still available (25 mg or 50 mg powder-solution), which may have encouraged back-switching. References: [1] Glintborg, et al. Arthritis Rheum2017;69(suppl 10). [2] Glintborg, et al. Abstract, EULAR2018. Acknowledgements: Partly sponsored by Biogen Disclosure of Interest: B. Glintborg Grant/research support from: Abbvie, Biogen, Pfizer, I. Sørensen: None declared, E. Omerovic: None declared, F. Mehnert: None declared, N. Manilo: None declared, K. Danebod: None declared, D. Jensen: None declared, H. Nordin: None declared, A. G. Loft Grant/research support from: AbbVie, MSD, Novartis, Pfizer, Roche, UCB, O. Hendricks Grant/research support from: Abbvie, Roche, Novartis, S. Chrysidis: None declared, B. Andersen: None declared, J. Raun: None declared, H. Lindegaard: None declared, J. Espesen: None declared, S. Jakobsen: None declared, I. M. Hansen Grant/research support from: Roche, E. Dalsgaard: None declared, D. Pedersen: None declared, S. Kristensen: None declared, A. Linauskas: None declared, L. Andersen: None declared, J. Grydehøj: None declared, N. Krogh: None declared, M. Hetland Grant/research support from: Abbvie, Biogen, BMS, CellTrion, MSD, Novartis, Orion, Pfizer, Samsung, UCB